Inducing interfacial progress based on a new sulfide-based composite electrolyte for all-solid-state lithium batteries. (1st December 2019) - Zhang, Hui; Li, Xiaohe; Hao, Shimeng; Zhang, Xian; Lin, Junpin
Abstract: Li10 GeP2 S12 -type sulfide solid electrolytes possess an obvious advantage in Li-ion conductivity, while show rather poor interfacial stability and compatibility against electrodes. Herein, the compositional tune via incorporating LiBr into Li10 GeP2 S12 matrix has been conducted to obtain a novel LiBr-Li10 GeP2 S12 composite electrolyte. It is interestingly found that high-conducting Li6 PS5 Br and Li10 GeP2 S12 co-exist, and Br substitution at the partial S sites of Li10 GeP2 S12 phase occurs in the composite electrolyte through the combination of Rietveld refinement against X-ray diffraction with Raman spectroscopy. In comparison with Li10 GeP2 S12 electrolyte itself, no appreciable change in ionic conductivity and activation barrier can be observed with respect to LiBr-Li10 GeP2 S12 composite electrolyte. While there is obvious improvement in interfacial conduction properties and chemical compatibility between cathode/anode and LiBr-Li10 GeP2 S12 electrolyte in terms of room-temperature interfacial resistances and temperature-dependence exchange current densities. Moreover, an all-solid-state cell containing the LiBr-Li10 GeP2 S12 composite electrolyte exhibits the distinct enhancement in discharge capacity and cycling stability during room-temperature galvanostatic cycling. In-situ electrochemical impedance spectroscopy measurements are discussed, suggesting that favorable interfacial modification of the cells can be provided in an internal way of the emergence of argyrodite Li6 PS5 Br in the new Li10 GeP2 S12 -based electrolyte materials. Graphical abstract: Image 103873 Highlights: Stable LiBr at high potential was incorporated into LGPS to obtain a new composite. Li6 PS5 Br phase & Br anion doping at the S sites of LGPS occurred in the composite. Detailed interfacial kinetics for the SEs against common electrodes were studied. Cycle capability of ASSLB at RT was obviously enhanced by using the composite SE. Insights were provided into valid effect of LiBr addition on cyclability of ASSLBs.